Farmer Field Book (FFB): a standard tool for monitoring agronomic and water management practices and productivity in cocoa farming systems - Esther, Narh; Dirwai, Tinashe Lindel; Zane, Giulia; Quarmine, William; Oke, Adebayo; Tilahun, Seifu A.; Schmitter, Petra (International Water Management Institute, 2025)
This report presents the development and prospective institutionalization of an integrated data collection tool, the Farmer Field Book (FFB), created to standardize agronomic monitoring across Ghana’s cocoa farming systems. Among persistent challenges such as low yields, climate variability, and inconsistent data availability, these instruments address critical data gaps by enabling systematic tracking of household information, irrigation practices, rainfed farm practices, and cocoa tree-level growth. Through its structured and consistent format, the tool supports evidence-based decision-making aimed at improving productivity, sustainability, and resilience within a sector largely driven by smallholder farmers.